From bioblasts to mitochondria: ever expanding roles of mitochondria in cell physiology - Brian O’Rourke (2010)
OPINION article Front. Physiol., 15 June 2010Sec. Mitochondrial Research https://doi.org/10.3389/fphys.2010.00007